Biomechanical analysis of backstroke swimming starts - De Jesus K. (2011)
The relationships between the start time and kinematic, kinetic and electromyographic data were examined in order to establish the common features of an effective backstroke swimming start. Complementarily, different starting positions were analysed to identify the parameters that account for the fastest backstroke start time under different constraints. 6 high-level swimmers performed 4×15m maximal trials of each start variants with different feet position: parallel and entirely submerged (BSFI) and above water surface (BSFE), being monitored with synchronized dual-media image, underwater platform plus handgrip with a load cell, and eletromyographic signal of Rectus Femoris and Gastrocnemius Medialis. Mean and SD values of start time for BSFI and BSFE were 2.03±0.19 and 2.14±0.36s, respectively. In both starts, high associations (r>=0.75, p<0.001) were observed between start time and centre of mass resultant average velocity at glide phase and horizontal impulse at take-off for BSFI, and centre of mass horizontal position at the start signal for BSFE. It was concluded that the greater impulse during the take-off and its transformation into a fast underwater movement are determinant to decrease the start time at BSFI. Regarding BSFE, a greater centre of mass pool-wall approximation might imply a flatter take-off angle, compromising underwater velocity and starting performance. © Georg Thieme Verlag KG Stuttgart - New York.